ANALISIS MANAJEMEN RANTAI PASOKAN PLASTIK STUDI PADA UMKM EDI PLASTIK KABUPATEN BANDUNG - Anton Mulyono Azis (Jurnal Bisnis Dan Kajian Strategi Manajemen, 2022)
There is uncertainty in the quality of raw materials delivered by suppliers to MSMEs Edi Plastik Bandung Regency, uncertainty in the quality of products delivered to consumers, information processing barriers regarding the decline in product prices in the market. The research was conducted at MSMEs Edi Plastik Bandung Regency which processed plastic waste into semi-finished goods. The research method used, namely descriptive methods with data collection techniques, namely through interviews and observations. The result of this study is that there are four actors involved in the supply chain. The flow of goods flows from upstream to downstream in the form of distribution of plastic waste raw materials from collectors and suppliers and distribution of products to consumers in the form of semi-finished products, while from downstream to upstream about returns and repairs. The flow of money uses two transactions, namely in cash, and transfers. The flow of information from downstream to upstream regarding capacity, delivery status, while from upstream to downstream regarding stock and ordering. Supervision of raw materials will overcome the uncertainty of raw material quality, the determination of product quality standards that can overcome the uncertainty of the products produced. The performance of MSMEs Edi Plastik Bandung Regency in the attributes of responsiveness, agility, and cost has achieved good performance. As for the reability and asset management attributes for asset turnover metrics are in the parity category.